Creep simulation of asymmetric effects by use of stress mode dependent weighting functions - Mahnken, Rolf (International Journal of Solids and Structures)

Dunkl Operators: Theory and Applications - Rösler, Margit (Lecture Notes in Mathematics)

The Karhunen-Loève expansion of improper complex random signals with applications in detection - Schreier, Peter J.; Scharf, Louis L. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
Non-stationary complex random signals are in general improper (not circularly symmetric), which means that their complementary covariance is non-zero. Since the Karhunen-Loeve expansion in its known form is only valid for proper processes, we derive the improper version of this expansion. It produces two sets of eigenvalues and an improper internal description. We use the Karhunen-Loeve expansion to solve the problem of detecting non-stationary improper complex random signals in additive white Gaussian noise. Using the deflection criterion we compare the performance of conventional processing, which ignores complementary covariances, with processing that takes these into account. The performance gain can be as great as a factor of 2.

Widely-linear beamforming - McWhorter, Todd; Schreier, Peter J. (Proc. 37th\ Asilomar Conf.\ Signals Syst.\ Computers)
In this paper we describe a beamforming algorithm based on widely-linear rather than linear data models. Initially, we develop this beamformer by generalizing the Capon (MVDR) optimization problem. That is, if the objective is to minimize output power while maintaining a specified directional gain, then we show that the output power of the widely-linear beamformer is less than or equal to the output power of the Capon (MVDR) beamformer. This result is valid regardless of the “true” distribution of the data. We also derive the widely-linear beamformer by considering beamforming to be an estimation problem. Linear models assume that the composite covariance matrix formed from the real and imaginary parts of the array-snapshot has a particular structure. This structure is often summarized by stating that the covariance formed from the array snapshot and its transpose (not Hermitian transpose) is zero. We could also call these data “proper” Gaussian vectors. The beamformers in this paper are appropriate for situations in which these implicit assumptions are violated.

Canonical coordinates are the right coordinate system for transform coding of noisy sources - Schreier, Peter J.; Scharf, Louis L.; Hu, Tianjian; Voran, Stephen D. (Proc.\ IEEE Works.\ Statistical Signal Proces.)
Historically, transform coding of noisy sources has been performed by first estimating the message and then quantizing this estimate. We show that it is also optimum to first transform the noisy observations into canonical coordinates, quantize, apply a Wiener filter in this coordinate system, and then transform the result back to the original coordinates. Canonical coordinates are uncorrelated, and quantizing and Wiener filtering are applied to each component independently. Optimality of this approach can be proved assuming additive white quantization noise. Half canonical coordinates minimize the mean-squared error by minimizing the trace of the error covariance matrix and full canonical coordinates maximize information rate by minimizing the determinant of the error covariance matrix.

A unified approach to performance comparisons between linear and widely linear processing - Schreier, Peter J.; Scharf, Louis L.; Mullis, Clifford T. (Proc.\ IEEE Works.\ Statistical Signal Proces.)
Recently, a number of papers have been published that show significant performance gains can be obtained by accounting for the fact that communication signals can be improper. In this paper, we derive a general result comparing the performance of conventional processing, which ignores the improper nature of signals, with processing that takes it into account. In particular, for an estimation and a detection problem, we find that the performance gain, as measured by mean-squared error and deflection, respectively, can be as large as a factor of 2, but no larger. In a communications example, we show how this finding generalizes the result that coherent processing enjoys a 3 dB gain over non-coherent processing.

Stochastic time-frequency analysis using the analytic signal: why the complementary distribution matters - Schreier, Peter J.; Scharf, Louis L. (IEEE Trans.\ Signal\ Process.)
We challenge the perception that we live in a “proper world”, where complex random signals can always be assumed to be proper (also called circularly symmetric). Rather, we stress the fact that the analytic signal constructed from a nonstationary real signal is, in general, improper, which means that its complementary correlation function is nonzero. We explore the consequences of this finding in the context of stochastic time-frequency analysis in Cohen’s class. There, the analytic signal plays a prominent role because it reduces interference terms. However, the usual time-frequency representation (TFR) based on the analytic signal gives only an incomplete signal description. It must be augmented by a complementary TFR whose properties we develop in detail. We show why it is still advantageous to use the pair of standard and complementary TFRs of the analytic signal rather than the TFR of the corresponding real signal.

Die Besteuerung von Beteiligungsveräußerungen und Rechtsformneutralität - Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Situierte Semantik. Die Rolle der Sprache und nicht-verbaler Strategien beim Erwerb räumlicher Relationen - Rohlfing, Katharina (Spracherwerb und Konzeptualisierung)

Situatedness: The interplay between context(s) and situation - Rohlfing, Katharina; Rehm, Matthias; Goecke, Karl Ulrich (Journal of Cognition and Culture)

A positive radial product formula for the Dunkl kernel - Rösler, Margit (Transactions of the American Mathematical Society)
It is an open conjecture that generalized Bessel functions associated with root systems have a positive product formula for non-negative multiplicity parameters of the associated Dunkl operators. In this paper, a partial result towards this conjecture is proven, namely a positive radial product formula for the non-symmetric counterpart of the generalized Bessel function, the Dunkl kernel. Radial hereby means that one of the factors in the product formula is replaced by its mean over a sphere. The key to this product formula is a positivity result for the Dunkl-type spherical mean operator. It can also be interpreted in the sense that the Dunkl-type generalized translation of radial functions is positivity-preserving. As an application, we construct Dunkl-type homogeneous Markov processes associated with radial probability distributions.

Episode aus dem Leben einer Künstlerin – Harriet Smithson, Hector Berlioz und die Symphonie fantastique - Grotjahn, Rebecca (Musik. Frau. Sprache. Interdisziplinäre Frauen- und Genderforschung an der Hochschule für Musik und Theater Hannover)

Frauenberuf Sängerin. Ein Thema musikwissenschaftlicher Frauen- und Geschlechterforschung - Grotjahn, Rebecca (Rheinische Sängerinnen des 20. Jahrhunderts. Eine Dokumentation in Wort und Ton)

Die Entdeckung der Terra incognita – Benjamin Bilse und sein reisendes Orchester - Grotjahn, Rebecca (Le Musicien et ses voyages. Pratiques, réseaux et représentations)

‚An der Spitze der musikalischen Bewegung‘ – Die Reisen der Bilse’schen Kapelle - Grotjahn, Rebecca (Neues Leben. Mitteilungsblatt der Deutschen Johann-Strauss-Gesellschaft e. V.)

‚Ein Lied wie dieses muss gebracht werden, ausgestattet – wie ein Theaterstück‘. Willi Forst und die Inszenierung des Singens - Grotjahn, Rebecca (Willi Forst. Ein Filmstil aus Wien)

Second-order analysis of improper complex random vectors and processes - Schreier, Peter J.; Scharf, Louis L. (IEEE Trans.\ Signal\ Process.)
We present a comprehensive treatment of the second-order theory of complex random vectors and wide-sense stationary (WSS) signals. The main focus is on the improper case, in which the complementary covariance does not vanish. Accounting for the information present in the complementary covariance requires the use of widely linear transformations. Based on these, we present the eigenanalysis of complex vectors and apply it to the problem of rank reduction through principal components. We also investigate joint properties of two complex vectors by introducing canonical correlations, which paves the way for a discussion of the Wiener filter and its rank-reduced version. We link the concepts of propriety and joint propriety to eigenanalysis and canonical correlation analysis, respectively. Our treatment is extended to WSS signals. In particular, we give a result on the asymptotic distribution of eigenvalues and examine the connection between WSS, proper, and analytic signals.

Structural Investigation of High-Valent Manganese–Salen Complexes by UV/Vis, Raman, XANES, and EXAFS Spectroscopy - Feth, Martin P.; Bolm, Carsten; Hildebrand, Jens P.; Köhler, Manuela; Beckmann, Oliver; Bauer, Matthias; Ramamonjisoa, Rivo; Bertagnolli, Helmut (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Sprachwahl – Textsorte – Dialogstruktur. Zu Verhörprotokollen aus Hexenprozessen des 17. Jahrhunderts. - Topalović, Elvira

Calcium Induced Shrinking of NaPA Chains: A SANS Investigation of Single Chain Behavior - Schweins, Ralf; Lindner, Peter; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Dilute solution behaviour of sodium polyacrylate chains in aqueous NaCl solutions - Schweins, Ralf; Hollmann, Jutta; Huber, Klaus (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Aggregation of a Pseudoisocyanine Chloride in Aqueous NaCl Solution - Herzog, Bernd; Huber, Klaus; Stegemeyer, Horst (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Preparation of Positively and Negatively Charged Organic Colloids from a Single Precursor - Röder, Thorsten; Kramer, Thomas; Huber, Klaus; Kitzerow, Heinz-Siegfried (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

Quasi-elastic scattering by semiflexible rings - Huber, Klaus; Stockmayer, Walter H.; Soda, Kunitsugu (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Monte Carlo calculations in comparison to neutron scattering studies: 3. On the structure of 12-arm star molecules - Huber, Klaus; Burchard, Walther; Bantle, Siegfried; Fetters, Lewis J. (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Monte Carlo calculations in comparison to neutron scattering studies: 2. Global dimensions of 12-arm stars - Huber, Klaus; Burchard, Walther; Bantle, Siegfried; J.^Fetters, Lewis (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Monte Carlo calculations in comparison to neutron scattering studies: 1. Linear chains - Huber, Klaus; Burchard, Walther; Bantle, Siegfried (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

First cumulant of the dynamic structure factor for rigid rings - Huber, Klaus; Stockmayer, Walter H. (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Albert Gier: Das Libretto - Tumat, Antje (Die Musikforschung)

Minimal discriminants for fields with small Frobenius groups as Galois groups - Fieker, Claus; Klüners, Jürgen (Journal of Number Theory)
We apply class field theory to the computation of the minimal discriminants for certain solvable groups. In particular, we apply our techniques to small Frobenius groups and all imprimitive degree 8 groups such that the corresponding fields have only a degree 2 and no degree 4 subfield.
Keywords: Algebra and Number Theory

Causality, Emergence, Self-Organisation

Globalization and Self-Organization in the Knowledge-Based Society - Fuchs, Christian (tripleC)

Co-operation and self-organisation - Fuchs, Christian (tripleC (Cognition, Communication, Co-operation))

The Role of the Individual in the Social information process - Fuchs, Christian (Entropy)

The Self-Organization of Matter - Fuchs, Christian (Nature, Society, and Thought)

Some Implications of Pierre Bourdieu’s Works for a Theory of Social Self-Organization - Fuchs, Christian (European Journal of Social Theory)

Structuration Theory and Self-Organization - Fuchs, Christian (Systemic Practice and Action Research)

Fortschritt und Utopie (Progress and utopia) - Fuchs, Christian (Vorschein)

Dialectical Materialism and the Self-Organization of Matter - Fuchs, Christian (Seeking Wisdom)

The Self-Organisation of Politics, Power and the Nation State. INTAS-Project “Human Strategies in Complexity“-Research Paper - Fuchs, Christian

The Architecture of the Information Society - Hofkirchner, Wolfgang; Fuchs, Christian (Proceedings of the 47th Annual Conference of the International Society for the Systems Sciences (ISSS): Agoras of the Global Village)

Dissertation ‚Muster ohne Wert’. Zur Funktionalisierung und Marginalisierung des Musters: https://d-nb.info/965565424/34 - Kraft, Kerstin

Dynamics of short-time-scale energy relaxation of optical excitations due to electron-electron scattering in the presence of arbitrary disorder - Meier, Torsten; Varga, I.; Thomas, P.; Koch, S.W. (Physical Review B)
A nonequilibrium occupation distribution relaxes towards the Fermi-Dirac distribution due to electron-electron scattering even in finite Fermi systems. The dynamic evolution of this thermalization process assumed to result from an optical excitation is investigated numerically by solving a Boltzmann equation for the carrier populations using a one-dimensional disordered system. We focus on the short-time-scale behavior. The logarithmically long time scale associated with the glassy behavior of interacting electrons in disordered systems is not treated in our investigation. For weak disorder and short range interaction we recover the expected result that the relaxation rate is enhanced by disorder. For sufficiently strong disorder, however, we find an opposite trend due to the reduction of scattering probabilities originating from the strong localization of the single-particle states. Long-range interaction in this regime produces a similar effect. The relaxation rate is found to scale with the interaction strength, however, the interplay between the implicit and the explicit character of the interaction produces an anomalous exponent.

Theory for the nonlinear optical response of semiconductor surfaces: Application to the optical Stark effect and spectral oscillations of the Si(111)-(2x1) surface exciton - Meier, Torsten; Reichelt, Matthias; Koch, S.W.; Rohlfing, M. (Physical Review B)
A microscopic approach is presented to compute nonlinear optical properties of semiconductor surfaces. The method uses quasiparticle wave functions and dispersions obtained from ab initio band-structure theory as an input for Bloch equations which describe the optical properties. Excitonic effects in the linear absorption spectra of the Si(111)- (2×1) surface are obtained by integrating equations of motion. To demonstrate the applicability of the approach for analyzing nonlinear optical properties, ultrafast light-intensity-dependent absorption changes of the surface exciton are predicted. The numerical results discuss the optical Stark effect and spectral oscillations of the surface exciton which can both be observed in pump-probe experiments.

Signatures of biexcitons and triexcitons in coherent non-degenerate semiconductor optics - Meier, Torsten; Sieh, C.; Finger, E.; Stolz, W.; Rühle, W.W.; Koch, S.W.; Thomas, P. (physica status solidi (b))
Signatures of exciton and two-exciton states in semiconductor systems are investigated experimentally and theoretically. A set of quantum well samples with different well widths is studied using coherent excitation spectroscopy. The experimental results are analyzed using a microscopic model demonstrating the importance of biexciton correlations and disorder effects. Additional numerical investigations of absorption changes in small nanorings are employed to analyze optical transitions from two-exciton to three-exciton resonances.

Martin Bock u.a. (Hg.): Un-verschämtes Glück. Auf der Suche nach dem Heil im Leben. Grundfragen des Glaubens Band 2, Seminare und Projekte für Erwachsene, Gütersloh 2002 - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

9. Sonntag nach Trinitatis. Mt 25,14-30: Die Angst vorm Verlieren verlieren - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien I/2)

Dynamics of short-time-scale energy relaxation of optical excitations due to electron-electron scattering in the presence of arbitrary disorder - Varga, Imre; Thomas, Peter; Meier, Torsten; Koch, Stephan W. (Physical Review B)
A nonequilibrium occupation distribution relaxes towards the Fermi-Dirac distribution due to electron-electron scattering even in finite Fermi systems. The dynamic evolution of this thermalization process assumed to result from an optical excitation is investigated numerically by solving a Boltzmann equation for the carrier populations using a one-dimensional disordered system. We focus on the short-time-scale behavior. The logarithmically long time scale associated with the glassy behavior of interacting electrons in disordered systems is not treated in our investigation. For weak disorder and short range interaction we recover the expected result that the relaxation rate is enhanced by disorder. For sufficiently strong disorder, however, we find an opposite trend due to the reduction of scattering probabilities originating from the strong localization of the single-particle states. Long-range interaction in this regime produces a similar effect. The relaxation rate is found to scale with the interaction strength, however, the interplay between the implicit and the explicit character of the interaction produces an anomalous exponent.

Electronic transport in a one-dimensional random array of scatterers - Meier, Torsten; Filinov, V.S.; Thomas, P.; Varga, I.; Bonitz, M.; Fortov, V.E; Koch, S.W. (Journal of Physics A: Mathematical and General)
The quantum dynamics of an ensemble of interacting electrons in an array of random scatterers is treated using a new numerical approach for the calculation of average values of quantum operators and time correlation functions in the Wigner representation. This approach combines both molecular dynamics and Monte Carlo methods and computes numerical traces and spectra of the relevant dynamical quantities such as momentum–momentum correlation functions and spatial dispersions. Considering, as an application, a system with fixed scatterers, the results clearly demonstrate that the many-particle interaction between the electrons can lead to an enhancement of the conductivity at intermediate densities.

Wigner approach to quantum dynamics simulations of the interacting carriers in disordered systems - Meier, Torsten; Filinov, V.; Thomas, P.; Bonitz, M.; Fortov, V.; Varga, I. (physica status solidi (b))
The new method for solving Wigner–Liouville's type equations and studying dynamics of quantum particles has been developed within the Wigner formulation of quantum statistical mechanics. This approach combines both molecular dynamics and Monte Carlo methods and computes traces and spectra of the relevant dynamical quantities. Considering, as an application, the quantum dynamics of an ensemble of interacting electrons in an array of random scatterers clearly demonstrates that the many-particle interaction between the electrons can lead to an enhancement of the electrical conductivity.

Semiconductor photonic-crystal structures: Optical spectra and carrier dynamics - Meier, Torsten

Studienbuch Informatik und Gesellschaft (Informatics and Society) - Fuchs, Christian; Hofkirchner, Wolfgang

The Autocreativity of Communication and the Re-Creativity of Actions in Social Systems - Fuchs, Christian; Stockinger, Gottfried (In Causality, Emergence, Self-Organisation)

Dialectical Philosophy and Self-Organisation - Fuchs, Christian (Causality, Emergence, Self-Organisation)

The Internet as a Self-Organizing Socio-Technological System. INTAS Project “Human Strategies in Complexity“-Research Paper - Fuchs, Christian

Globalization and Self-Organization. INTAS-Project “Human Strategies in Complexity”-Research Paper - Fuchs, Christian

Co-Operation in Complex, Self-organising Systems. INTAS-Project “Human Strategies in Complexity“-Research Paper - Fuchs, Christian

Co-operation in Complex, Self-organising, Information-Generating Systems - Fuchs, Christian (Proceedings of the 47th Annual Conference of the International Society for the Systems Sciences (ISSS): Agoras of the Global Village)

‚Kleider machen Leute. Kleidung als Abbild bürgerlicher Werte und Tugenden’ - Kraft, Kerstin

‚Akademisches Puppenspielen? – Für eine objekt-basierte Bekleidungsforschung’ - Kraft, Kerstin

‚Bürgerliche Kleidung von Innen und Außen’ - Kraft, Kerstin

Recent Advances in the Synthesis of Mesostructured Aluminum Phosphates - Tiemann, Michael; Fröba, Michael (Host‐Guest‐Systems Based on Nanoporous Crystals)
Recent Advances in the Synthesis of Mesostructured Aluminium Phosphates...

Masking and etching of silicon and related materials for geometries down to 25 nm - Hilleringmann, Ulrich; Vieregge, T.; Horstmann, J.T. (IECON'99. Conference Proceedings. 25th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.99CH37029))

Matching analysis of NMOS-transistors with a channel length down to 30 nm - Horstmann, J.T.; Hilleringmann, Ulrich; Goser, K. (IECON'99. Conference Proceedings. 25th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.99CH37029))

Negative differential resistance in ultrashort bulk MOSFETs - Wirth, G.; Hilleringmann, Ulrich; Horstmann, J.T.; Goser, K. (IECON'99. Conference Proceedings. 25th Annual Conference of the IEEE Industrial Electronics Society (Cat. No.99CH37029))

Nanometer scale organic thin film transistors with Pentacene - Pannemann, Ch.; Diekmann, T.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Microscopic theory for the nonlinear optical response of semiconductor surfaces: Application to the optical Stark effect of the Si(111)-(2x1) surface exciton - Meier, Torsten; Reichelt, Matthias; Koch, S.W.; Rohlfing, M. (physica status solidi (b))
A novel microscopic approach for computing nonlinear optical properties of semiconductor surfaces is outlined. The linear and nonlinear response of the Si(111)-(2×1) surface is studied using a combination of ab-initio band-structure theory and equation of motion technique. The usefulness of the method is shown by reproducing known excitonic effects in the linear differential reflectivity spectrum. To additionally demonstrate the applicability of the approach for the nonlinear regime, the nonlinear optical response in Stark effect configuration is examined.

Semiconductor excitons in photonic crystals - Meier, Torsten; Eichmann, R.; Pasenow, B.; Thomas, P.; Koch, S.W. (physica status solidi (b))
Optical properties of a semiconductor quantum well in the vicinity of a two-dimensional photonic crystal are investigated. Due to the periodic spatial modulation of the dielectric environment the effective Coulomb interaction potential exhibits the periodicity of the photonic crystal. As a consequence, the excitonic binding energy varies periodically by up to 50% depending on the spatial position of the exciton relative to the structured dielectric. The self image charge effects result in a position dependent shift of the single-particle bandgap such that the spectral position of the absorption spectrum also develops the periodicity of the photonic surrounding.

Semiconductor absorption in photonic crystals - Eichmann, R.; Pasenow, B.; Meier, Torsten; Stroucken, T.; Thomas, P.; Koch, S.W. (Applied Physics Letters)
Absorption spectra of semiconductor structures in photonic crystal environments are investigated numerically. It is shown that the periodic dielectric structuring changes the local optical and Coulomb interaction properties of semiconductor electron–hole excitations. The structurally induced modifications offer the possibility to design important aspects of the optoelectronic semiconductor properties.

Echos in Festkörpern - Meier, Torsten; Thomas, P. (Physik Journal)

Mission als Ver-Fahren. Praktisch-theologische Anmerkungen zu einer performativen Religionspädagogik - Schroeter-Wittke, Harald (Mission als Dialog. Zur Kommunikation des Evangeliums heute)

Henning Schröer: In der Verantwortung gelebten Glaubens. Praktische Theologie zwischen Wissenschaft und Lebenskunst

Gottesdienst in der Zeit - Schroeter-Wittke, Harald (Liturgisches Kompendium)

Populäre Kultur und Religion

Die andere Barth. Religionspädagogische Ansichten zum fehlenden Bild von Carola Barth (1879-1959) - Schroeter-Wittke, Harald (Theologie als Vermittlung. Bonner evangelische Theologen des 19. Jahrhunderts im Proträt. Friedrich Wintzer zum 70. Geburtstag)

"Im Spiel üben wir, verlieren zu können". Über den Zusammenhang von Spielkultur, Spieleentwicklung und theologischem Spielwitz - Schroeter-Wittke, Harald (Spiel und Religion. Hartmut Meesmann im Gespräch mit Hans Saner, Harald Schroeter-Wittke und Susanne Wolf-Withöft)

Marcello D'Orta: Religion und Pädagogik in Neapel - ein Reisegespräch - Schroeter-Wittke, Harald; D'Orta, Marcello (Reisen. Fährten für eine Theologie unterwegs. Hans-Martin Gutmann zum 50. Geburtstag)

Daneben reisen - ins Paradiesseits. Reiseführer als Religionspädagogen - Schroeter-Wittke, Harald (Reisen. Fährten für eine Theologie unterwegs. Hans-Martin Gutmann zum 50. Geburtstag)

Performance als religionsdidaktische Kategorie. Prospekt einer performativen Religionspädagogik - Schroeter-Wittke, Harald (Schauplatz Religion. Grundzüge einer Performativen Religionspädagogik)

Unterhaltung als Theologie - Theologie als Unterhaltung. Thesen zur theologischen Wahrnehmung von Entertainment - Schroeter-Wittke, Harald (Popularmusik und Kirche - Positionen, Ansprüche, Widersprüch)

Unterhaltung als Theologie - Theologie als Unterhaltung. Homiletische und religionspädagogische Anmerkungen zur zeitgenössischen Gestaltung von Theologie - Schroeter-Wittke, Harald (Deutsches Pfarrerblatt)

Ur-Sprung im dunklen Licht. Eine resonante Begehung von Bill Violas Video-Installation "Five Angels for the Millenium" im Gasometer Oberhausen - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/24/hsw2.htm)

Intakt und Ekstase. Praktisch-theologische An- und Vorschläge zum Rhythmus. Eine reflexive Suite - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/23/hsw1.htm)

Übergang statt Untergang. Victor Turners Bedeutung für eine kulturtheologische Praxistheorie - Schroeter-Wittke, Harald (Theologische Literaturzeitung)

Kirchentag als ManiFest. Beobachtungen zur öffentlichen Bibeldidaktik nach 1945 - Schroeter-Wittke, Harald (Jahrbuch für Biblische Theologie)

Gott unterhält uns! Bibelarbeit als kultureller Bibelgebrauch - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

Kirchentag - Schroeter-Wittke, Harald (Typisch evangelisch - Typisch katholisch)

Kirchengeschichte(n) am Wohnort - Schroeter-Wittke, Harald; Dronsz, Gesine (Katechetische Blätter)

Thesen zu einer Praktischen Theologie der Popkultur - Schroeter-Wittke, Harald (Praktische Theologie)

Reisen. Fährten für eine Theologie unterwegs. Hans-Martin Gutmann zum 50. Geburtstag

Blasphemie als Problem der Frömmigkeit. Zur christlichen Wahrnehmung der Verletzung religiöser Gefühle im Horizont von Popmusik (23 Thesen) - Schroeter-Wittke, Harald (Popularmusik und Kirche - Positionen, Ansprüche, Widersprüch)

Vom Spiel mit sozialen Rollen. Zur literarischen Darstellung emotioanler Kompensationsstrategien in Katja Lange-Müllers Erzählung "Verfrühte Tierliebe" - Müller, Inez (literatur für leser)

Many-body Coulomb effects in the optical properties of semiconductor heterostructures - Meier, Torsten; Pasenow, B.; Thomas, P.; Koch, S.W. (Germany NIC Series, Vol. 20)

Stable vector bundles on a rational curve with one node - Burban, Igor (Ukrain. Mat. Zh.)

Querpässe. Beiträge zur Kultur-, Literatur- und Mediengeschichte des Fußballs

Die Wirklichkeit in der Wirklichkeit. Fernsehfußball und mediale Wissenskultur - Adelmann, Ralf; Stauff, Markus (Querpässe. Beiträge zur Kultur-, Literatur- und Mediengeschichte des Fußballs)

Fußball, kulturwissenschaftlich! - Adelmann, Ralf; Parr, Rolf; Schwarz, Thomas (Querpässe. Beiträge zur Kultur-, Literatur- und Mediengeschichte des Fußballs)

Rezension von: Friedrich Kittler: Optische Medien. Berliner Vorlesung 1999 - Adelmann, Ralf (Sehepunkte)

Im Acker der Geschichten. Formen historischer Sinnstiftung in Claude Simons "Les Géorgiques" - Schreckenberg, Stefan

Visuelle Kulturen der Kontrollgesellschaft. Zur Popularisierung digitaler und videografischer Visualisierungen im Fernsehen - Adelmann, Ralf